The Authoritative historian : tradition and innovation in Ancient historiography - Kingsley, K. Scarlett; Monti, Giustina; Rood, Tim (Cambridge : Cambridge University Press, 2022)
In this volume an international group of scholars revisits the themes of John Marincola's ground-breaking Authority and Tradition in Ancient Historiography. The nineteen chapters offer a series of case studies that explore how ancient historians'approaches to their projects were informed both by the pull of tradition and by the ambition to innovate. The key themes explored are the relation of historiography to myth and poetry; the narrative authority exemplified by Herodotus, the'father'of history; the use of'fictional'literary devices in historiography; narratorial self-presentation; and self-conscious attempts to shape the historiographical tradition in new and bold ways. The volume presents a holistic vision of the development of Greco-Roman historiography and the historian's dynamic position within this practice.
Introduction: The Authoritative Historian -- Part I, Myth, Fiction, and the Historian's Authority -- 1, Seven Types of Fiction in the Greek Historians -- 2, Folktale and Local Tradition in Charon of Lampsacus -- 3, Mythical and Historical Time in Herodotus: Scaliger, Jacoby, and the Chronographic Tradition -- 4, Myth and History in Livy's Preface -- Part II, Dislocating Authority in Herodotus' Histories -- 5, Herodotus as Tour Guide: The Autopsy Motif -- 6, Interpretive Uncertainty in Herodotus's Histories -- 7, "It is no accident that...": Connectivity and Coincidence in Herodotus -- 8, Through Barbarian Eyes: Non-Greeks on Greeks in Herodotus -- Part III, Performing Collective and Personal Authority -- 9, Singing and Dancing Pindar's Authority -- 10, Authority, Experience, and the Vicarious Traveller in Herodotus' Histories -- 11, Veni, vidi, vici: Whed did Roman Politicians use the First-Person Singular? -- 12, Self-Praise and Self-Presentation in Plutarch -- Part IV, Generic Transformations -- 13, Thucydides' Mytilenaean Debate: Political Philosophy or Authoritative History? -- 14, Tradition, Innovation, and Authority: Caesar's Historical Ambitions -- 15, Tradition and Authority in Philostratus' Lives of the Sophists -- Part V, Innovation within Tradition -- 16, "When one assumes the ethos of writing history": Polybius' Historiographical Neologisms -- 17, How Tradition is Formed: From the Fall of Caesar to the Rise of Octavian -- 18, Burn, Baby, Burn (Disco in Furneaux): Tacitean Authority, Innovation, and the Neronian Fire (Annals 15.38-9) -- 19, The Authority to be Untraditional
Elektronická reprodukce.
Keywords: historiografie -- starověký Řím; historiografie -- starověké Řecko; historiography -- ancient Rome; historiography -- ancient Greece; e-knihy online; sborníky; studie; e-books online; papers of several authors; studies